Epidemiological analysis of hospitalizations of individuals in university- age range due to headaches in the municipality of Barbalha, Ceara - Davi, Emanuela Freire Caetano; Melo, Leonardo José Rodrigues de Araújo; Junior, Francisco Duque de Paiva Giudice; Santos, Leonardo Elias Araujo dos; Sousa, João Marcelo Albuquerque Beserra de; Rodrigues, Pedro Vitor Ferreira; Aureliano, Kauane Emilly Ribeiro; Rosa, Rodrigo Fagundes da; Tavares, Mariana Alcântara (Headache Medicine, 2023)
Full abstract in PDF.